Low Rate of Acquired Linezolid Resistance in Multidrug-Resistant Tuberculosis Treated With Bedaquiline-Linezolid Combination - Du, Jian; Gao, Jingtao; Yu, Yanhong; Li, Qingfeng; Bai, Guanghong; Shu, Wei; Gao, Mengqiu; Liu, Yuhong; Wang, Lu; Wang, Yufeng; Xue, Zhongtan; Huo, Fengmin; et al. (Frontiers in Microbiology, 2021)
In this retrospective study in China, we aimed to: 1) determine the prevalence of linezolid (LZD) resistance among multidrug-resistant tuberculosis (MDR-TB)-infected patients; 2) monitor for dynamic LZD susceptibility changes during anti-TB treatment and 3) explore molecular mechanisms conferring LZD resistance. A total of 277 MDR-TB patients receiving bedaquiline (BDQ)-containing regimens in 13 TB specialized hospitals across China were enrolled in the study. LZD and BDQ susceptibility rates were determined using the minimum inhibitory concentration (MIC) method, then DNA sequences of patient isolates were analyzed using Sanger sequencing to detect mutations conferring LZD resistance. Of 277 patients in our cohort, 115 (115/277, 41.5%) with prior LZD exposure yielded 19 (19/277, 6.9%) isolates exhibiting LZD resistance. The LZD resistance rate of LZD-exposed group isolates significantly exceeded the corresponding rate for non-exposed group isolates (P = 0.047). Genetic mutations were observed in 10 (52.6%, 10/19) LZD-resistant isolates, of which a Cys154Arg (36.8%, 7/19) substitution within ribosomal protein L3 was most prevalent. Analysis of sequential positive cultures obtained from 81 LZD-treated patients indicated that cultured organisms obtained from most patients (85.2%, 69/81) retained original LZD MIC values; however, organisms cultured later from two patients exhibited significantly increased MIC values that were attributed to the rplC substitution T460C. Overall, LZD resistance was detected in 6.9% of patients of an MDR-TB cohort in China. Low rate of acquired LZD resistance was noted in MDR-TB treated with BDQ-LZD combination.